2018
DOI: 10.1007/s00345-018-2384-6
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-invasive bladder cancer organ-preserving therapy: systematic review and meta-analysis

Abstract: We found no differences in overall survival and progression-free survival between these two interventions. Nonetheless, we found that cancer-specific survival favored patients who received radical cystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 37 publications
0
23
1
1
Order By: Relevance
“…Fahmy et al ( 13 ) indicated that the OS and disease-specific survival (DSS) were comparable between TMT and RC: the average 10-year OS rate was 30.9% for TMT and 35.1% for RC, respectively ( P = 0.32), and the average 10-year DSS rate was 50.9% for TMT and 57.8% for RC, respectively ( P = 0.26). García-Perdomo et al ( 15 ) reported that CSS rate favored patients who underwent RC. However, most included studies were case series in the systematic reviews by Arcangeli et al ( 14 ) and Fahmy et al ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fahmy et al ( 13 ) indicated that the OS and disease-specific survival (DSS) were comparable between TMT and RC: the average 10-year OS rate was 30.9% for TMT and 35.1% for RC, respectively ( P = 0.32), and the average 10-year DSS rate was 50.9% for TMT and 57.8% for RC, respectively ( P = 0.26). García-Perdomo et al ( 15 ) reported that CSS rate favored patients who underwent RC. However, most included studies were case series in the systematic reviews by Arcangeli et al ( 14 ) and Fahmy et al ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several clinical trials compared the outcomes between RC and TMT ( 10 12 ). Most of the literature included in the previous meta-analysis were case series ( 9 , 13 , 14 ) and did not directly compare the efficacy of RC and TMT; and not all included patients were performed standard TMT in the other meta-analysis ( 15 ). So, it is essential to perform a meta-analysis directly comparing RC and standard TMT.…”
Section: Introductionmentioning
confidence: 99%
“…In a 2015 review by Arcangeli et al [8], CMT was not associated with a statistically significant survival advantage (5‐year OS: 57% vs 52%, P = 0.4). Similarly, in a 2018 systematic review by Garcia‐Perdomo et al [7] no difference in OS was found between CMT or RC (hazard ratio [HR] 1.06, 95% CI 0.85–1.31); however, DSS was better in the RC arm (HR 1.23; 95% CI 1.04–1.46).…”
Section: Introductionmentioning
confidence: 90%
“…Other reviews have been conducted analysing RC vs CMT without the use of BT [7,8]. In a 2015 review by Arcangeli et al [8], CMT was not associated with a statistically significant survival advantage (5‐year OS: 57% vs 52%, P = 0.4).…”
Section: Introductionmentioning
confidence: 99%
“…Radical cystectomy (RC) with cisplatin-based neoadjuvant chemotherapy (NAC) is the standard of care for the management of muscleinvasive BCa (MIBC). In recent years, bladder-preserving strategies combining bladder tumor transurethral resection (TURB) with radiotherapy and concurrent radio-sensitizing chemotherapy, also known as trimodal therapy (TMT), have shown similar results and reduced morbidity as compared to RC in selected MIBC patients (2,3). As a result, current guidelines now recommend both RC and TMT as effective treatment options for MIBC (4)(5)(6)(7).…”
mentioning
confidence: 99%